Direct current electrodeposition of Zn and Zn–SiC nanocomposite coatings. (July 2014) - Sajjadnejad, M.; Omidvar, H.; Javanbakht, M.; Pooladi, R.; Mozafari, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Pure Zn and Zn matrix composite coatings containing nano-sized SiC particles with an average size of 50 nm were prepared from the zinc sulphate bath. The effect of the particle concentration and current density on the amount of particles embedded was examined. Electron microscopic studies revealed that the coating morphology was modified by the presence of SiC nanoparticles. Corrosion resistance properties of the coatings were studied using a potentiodynamic polarisation technique in 1M NaCl solution. It was established that agglomeration of nanoparticles worsens corrosion resistance properties of Zn–SiC coatings. However, the presence of well dispersed nanoparticles significantly improves the corrosion resistance of the zinc. Incorporation of SiC nanoparticles also improves the microhardness of the zinc matrix.